ICT Validation Methodologies for Logistics Management - Cano, Jose Alejandro; Salazar, Fernando; Montoya, Rodrigo Andrés GÓMEZ- (ExcelingTech, 2020)
This article aims to characterize the main methodologies for validating the implementation of ICT in logistics processes to support the decision-making process to select the ICT that best suits to logistics processes in a firm. For this, the characterization of models such as TAM, UTAUT, DART, DMAIC, AMEF, and QDF is presented. The study concludes that the implementation and appropriation of ICT in logistics processes requires adequate selection and validation, for which reference frameworks must be used to structure and design robust technological solutions according to the real problems faced by each firm, and that in turn, support decision-making on the selection of the most appropriate technologies generating the greatest benefit and low risks to logistics processes.